2021
DOI: 10.3390/diagnostics11122256
|View full text |Cite
|
Sign up to set email alerts
|

Dilated Odontoma Arising in the Mandibular Third Molar Germ: Report of a Case of an Unusual Lesion in an Uncommon Site

Abstract: Dilated odontoma is the most severe variant of dens invaginatus. It is extremely uncommon in the posterior mandible. It is thought to originate during the morpho-differentiation stage of dental development. However, its etiology and pathogenesis remain obscure. We report here the clinical and pathologic findings of an incidentally discovered dilated odontoma arising in the left third mandibular molar germ of an 11-year-old male and a review of the pertinent literature. As dilated odontoma is not established as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The results obtained showed that Dilated Odontoma was present in the lower third molar region, which has been rarely described or cited by authors in the literature [10]. The literature [4] also mentions the rarity of dens invaginatus in the mandible, mainly citing the molar region.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The results obtained showed that Dilated Odontoma was present in the lower third molar region, which has been rarely described or cited by authors in the literature [10]. The literature [4] also mentions the rarity of dens invaginatus in the mandible, mainly citing the molar region.…”
Section: Discussionmentioning
confidence: 91%
“…Dens invaginatus (DI) is an abnormality of tooth development that results from the enfolding of the enamel organ into the dental papilla before the completion of calcification. Oehler's widely accepted classification system divides this malformation into three simple categories: class I, II, III a and b [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations